Efficacy and safety of transanal endoscopic microsurgery for early rectal cancer: a meta-analysis - Wang, Chunqiang; Huang, Tianye; Wang, Xuebing (Frontiers in Oncology, 2025)
BackgroundThe gold standard for the treatment of rectal cancer is radical surgery with total mesorectal excision (TME). As one of the alternatives to radical surgery, local resection has been proposed for the treatment of early rectal cancer. The purpose of this article was to evaluate the safety and efficacy of transanal endoscopic microsurgery (TEM) in the treatment of early rectal cancer.MethodsBy searching the PubMed, Cochrane Library, Web of Science, and China National Knowledge Infrastructure databases, we selected all articles on TEM for early rectal cancer. Two researchers independently completed the entire process from screening, inclusion to data extraction and performed statistical analysis using RevMan 5.3. The primary outcomes included basic patient characteristics, overall survival rate, disease-free survival rate, disease-specific survival rate, recurrence rate, and complication rate and type.ResultsA total of 33 articles were included in this meta-analysis. The results showed that the overall survival rate was 100% for T0 stage, 98.1% for Tis (carcinoma in situ) stage, and 80.2% for early stage rectal cancer patients (83.9% for T1 and 72.4% for T2). The weighted overall survival rate was 94% (RD = 0.94, 95% CI = 0.93–0.95, I2 = 80%, P < 0.00001) for all stage patients, the weighted disease-free survival rate was 91% (RD = 0.91, 95% CI = 0.90–0.93, I2 = 83%, P < 0.00001), and the disease-specific survival rate was 97% (RD = 0.97, 95% CI = 0.96–0.98, I2 = 63%, P < 0.00001). The recurrence rate was 0.5% for T0 stage, 1.9% for Tis stage, and 11.9% for early stage rectal cancer patients (8.1% for T1 and 19.7% for T2). The weighted recurrence rate was 7% (RD = 0.07, 95% CI = 0.06–0.08, I2 = 69%, P < 0.00001) for all stage patients. The weighted complications rate was 11% (RD = 0.11, 95% CI = 0.10–0.12, I2 = 66%, P < 0.00001) for all stage patients, with Clavien-Dindo grade I accounting for 77.7%, Clavien-Dindo grade II accounting for 8%, and Clavien-Dindo grade III accounting for 14.3%.ConclusionThe results showed that TEM has a high postoperative survival rate, low recurrence rate, and low complication rate in the T0 stage, Tis stage, and T1 stage, indicating its good safety and efficacy. For the treatment of T2 stage, TEM has a lower overall survival rate and a higher recurrence rate. Our meta-analysis results suggest that TEM alone is not recommended as a curative treatment for T2 stage; on the contrary, TME is more frequently recommended.